The City of Johannesburg can end AIDS by 2030 : Modelling the Impact of Achieving the Fast-Track Targets and What it Will Take to Get There - Stuart, Robyn M. (Wiley, 2019)
In 2014, city leaders from around the world endorsed the Paris Declaration on Fast‐Track Cities, pledging to achieve the 2020 and 2030 HIV targets championed by UNAIDS. The City of Johannesburg – one of South Africa's metropolitan municipalities and also a health district – has over 600,000 people living with HIV (PLHIV), more than any other city worldwide. We estimate what it would take in terms of programmatic targets and costs for the City of Johannesburg to meet the Fast‐Track targets, and demonstrate the impact that this would have.